Pattern and Epidemiology of Poisoning in the East African Region: A Literature Review - Dexter Tagwireyi; Patience Chingombe; Star Khoza; Mandy Maredza (Journal of Toxicology)
The establishment and strengthening of poisons centres was identified as a regional priority at the first African regional meeting on the Strategic Approach to International Chemicals Management (SAICM) in June 2006. At this meeting, the possibility of a subregional poisons centre, that is, a centre in one country serving multiple countries, was suggested. The WHO Headquarters following consultation with counterparts at the WHO Regional Office for Africa (AFRO) and the SAICM Africa Regional Focal Point successfully submitted a proposal to the SAICM Quick Start Programme (QSP) Trust Fund Committee for a feasibility study into a subregional poisons centre in the Eastern Africa subregion. However, before such a study could be conducted it was deemed necessary to carry out a literature review on the patterns and epidemiology of poisoning in this region so as to inform the feasibility study. The current paper presents the results of this literature review. The literature search was done in the months of June and July 2012 by two independent reviewers with no language or publication date restrictions using defined search terms on PUBMED. After screening, the eventual selection of articles for review and inclusion in this study was done by a third reviewer.